The genus Zambedania Mahunka 1972 (Acari: Heterostigmatina: Pygmephoridae)—redescription of the type species Z. africana and descriptions of two new species from Africa and South America - Camerik, Anne M.; Magowski, Wojciech Ł. (Zootaxa, 2014)
The type species of the genus Zambedania Mahunka, 1972 (Z. africana Mahunka, 1972) is redescribed based on the holotype collected from soil in Zimbabwe. Two new species are described and illustrated herewith: Z. madagascariana from Madagascar and Z. argentiniana from Argentina. The generic diagnosis of Zambedania is amended, and the key to its species is supplied. Morphology, taxonomy and biology of included species are briefly discussed. The first record of the genus being phoretic on a South American nemesiid spider is presented.